Catheter-Related Bladder Discomfort: How Can We Manage It? - Jang, Eun Bi; Hong, Seong Hwi; Kim, Kyu Shik; Park, Sung Yul; Kim, Yong Tae; Yoon, Young Eun; Moon, Hong Sang (International neurourology journal, 2020)
The urethral catheter is used in various clinical situations such as diagnosing urologic disease, urine drainage in patients after surgery, and for patients who cannot urinate voluntarily. However, catheters can cause numerous adverse effects, such as catheter-associated infection, obstruction, bladder stones, urethral injury, and catheter-related bladder discomfort (CRBD). CRBD symptoms vary among patients from burning sensation and pain in the suprapubic and penile areas to urinary urgency. CRBD significantly reduces patient quality of life and can lead to several complications. CRBD is caused by catheter-induced bladder irritation due to muscarinic receptor-mediated involuntary contractions of bladder smooth muscle and also can be caused by mechanical stimulus of the urethral catheter. Various pharmacologic studies for managing CRBD, including antimuscarinic and antiepileptic agents and botulinum toxin injections have been reported. If urologists can reduce patients’ CRBD, their quality of life and recovery can improve.